2004
DOI: 10.1101/gr.2094104
|View full text |Cite
|
Sign up to set email alerts
|

Novel RNAs Identified From an In-Depth Analysis of the Transcriptome of Human Chromosomes 21 and 22

Abstract: In this report, we have achieved a richer view of the transcriptome for Chromosomes 21 and 22 by using high-density oligonucleotide arrays on cytosolic poly(A) + RNA. Conservatively, only 31.4% of the observed transcribed nucleotides correspond to well-annotated genes, whereas an additional 4.8% and 14.7% correspond to mRNAs and ESTs, respectively. Approximately 85% of the known exons were detected, and up to 21% of known genes have only a single isoform based on exon-skipping alternative expression. Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
377
1
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(404 citation statements)
references
References 35 publications
14
377
1
12
Order By: Relevance
“…Later, Modrek and Lee (2002) anticipated that 40 to 60% of the genes undertake alternative splicing forms and the frequency of this event should be identical between mammals, flies and worms (Brett et al, 2002). This number increased to 74% in a study using microarrays (Johnson et al, 2003) and was corroborated by the analysis of the transcriptome of human chromosomes 21 and 22 which showed that alternative splicing occurs in more than 80% of the genes (Kampa et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Later, Modrek and Lee (2002) anticipated that 40 to 60% of the genes undertake alternative splicing forms and the frequency of this event should be identical between mammals, flies and worms (Brett et al, 2002). This number increased to 74% in a study using microarrays (Johnson et al, 2003) and was corroborated by the analysis of the transcriptome of human chromosomes 21 and 22 which showed that alternative splicing occurs in more than 80% of the genes (Kampa et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Bioinformatics analysis of human genome indicates that more than 75% of human genes are alternatively spliced (Johnson et al, 2003;Kampa et al, 2004). Alternative splicing plays a critical role in controlling differentiation and development , and misregulation of alternative splicing is the cause of many life-threatening human diseases (Faustino and Cooper, 2003;Stoilov et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent highthroughput analysis has demonstrated that the majority of human genes are subjected to splicing variations (Kampa et al, 2004). Thus, alternative splicing appears to be a major regulator of post-transcriptional modifications and may cause a significant change in the function of the encoded protein.…”
Section: Introductionmentioning
confidence: 99%